Free Vascularized Medial Femoral Condyle Corticocancellous Flap for Treatment of Challenging Upper Extremity Nonunions - Fei, Wu; Danmou, Xing; Dong, Ren; Wei, Feng; Eberlin, Kyle R.; Yan, Chen; Wusheng, Kan (Journal of Reconstructive Microsurgery, 2015)
Background Nonunions in the upper extremity are challenging for the reconstructive surgeon. The evolution of microsurgical techniques has allowed for the reliable use of free vascularized bone flaps.Methods In a retrospective study, patients with challenging upper limb nonunions who underwent free vascularized corticocancellous flaps from the medial femoral condyle (MFC) were included. Patient demographics, surgical technique, and outcomes were evaluated.Results Fifteen patients with nonunions of the upper extremity underwent free MFC corticocancellous flap reconstruction. The length of preoperative bone defects ranged from 0.8 to 3 cm, and the mean number of procedure prior to free MFC reconstruction was 1.5. Thirteen patients healed completely in an average of 15 weeks (range, 8–22 weeks). Two patients were lost to follow-up. Only one patient required additional surgery. Functional outcome measures such as Mayo, Disability of Arm, Shoulder, and Hand, and Constant–Murley scores all demonstrated improvement.Conclusion The free vascularized MFC corticocancellous flap can be successfully used for challenging upper extremity nonunions and small bone defects.
Keywords: upper extremity; nonunion; free vascularized corticocancellous flap